2015
DOI: 10.4038/amj.v9i2supp.7553
|View full text |Cite
|
Sign up to set email alerts
|

Responsive feeding practices among caregivers in rural Anuradhapura; a missing component in infant feeding!

Abstract: BackgroundResponsive feeding (RF) is a strategy that has a positive impact on growth, caregiver behaviours and dietary intake of children. But concern given to RF in national nutrition programmes is inadequate. Our aim is to explore the knowledge and practices on RF among mothers having infants of 9 months in Nuwaragam Palatha Central (NPC) MOH area, Anuradhapura. MethodsWe conducted a qualitative study using in-depth interviews with mothers who were purposefully selected to represent different socio-demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, many primary health care workers are unaware of it making RF the missing link in the current nutrition program [13]. Previous studies showed the knowledge on the RF among mothers as well as Public Health Midwives (PHM) are inadequate [14,15]. Sri Lankan study showed the RF practices improve eating behaviors and child growth [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, many primary health care workers are unaware of it making RF the missing link in the current nutrition program [13]. Previous studies showed the knowledge on the RF among mothers as well as Public Health Midwives (PHM) are inadequate [14,15]. Sri Lankan study showed the RF practices improve eating behaviors and child growth [16].…”
Section: Introductionmentioning
confidence: 99%
“…Not all distractions may be considered to be negative, however: short, but intentional distractions may be positive if effectively used to refocus a child during feeding (Moore et al, 2006 ). In our study and others in Sri Lanka, however, distractions were not brief, but employed throughout entire feeding episodes and often resulted in children moving around the house (Lucas et al, 2021 ; Senevirathne et al, 2015 ). Ensuring consistent mealtime structures, such as having a fixed location for eating and using minimal distractions, may be associated with less food fussiness during feeding (Finnane et al, 2017 ).…”
Section: Discussionmentioning
confidence: 60%
“…Our study found that 86% of infants between 6-24 months were fed in a specific place similar to Jeyakumaran's study in Jaffna (80%). Responsive feeding, including feeding in a specific place, in seated position, with a non-distractive environment, according to hunger cues, at a regular time, while responding to the child in an emotionally supportive manner without forcing, scolding or physical restraint were seen in all infants at the initiation of CF, with a lowest of 79% at 6-8 months which improved to 93% by 2 years in contrast to the previous reported studies where authoritarian feeding style was used in 82% care givers of children aged 3-5 years in Colombo 13 , knowledge regarding responsive feeding was seen in only 25-49% caregivers of infants aged 4-12 months in Bibile 14 , responsive feeding was not effectively practised 9 months of age according to a qualitative study in Anuradhapura 15 , 64% of preschool teachers agreed that force feeding was necessary in Nuwara Eliya 16 and where only 22.7% used responsive feeding in children between 4-23 months in Jaffna 17 . Individualized counselling, which was the key difference between our study population and the DHS 2016/2017 group as well as the other reported studies, is the most likely reason for the high adherence to IYCF guidelines in our study population, which also enabled our study population to achieve the 2020 IYCF national targets.…”
Section: Discussionmentioning
confidence: 63%